THE MEDIATING EFFECT OF THE KEY SUPPLIER RELATIONSHIP MANAGEMENT PRACTICES IN THE RELATIONSHIP BETWEEN THE SUPPLY CHAIN ORIENTATION AND THE ORGANIZATIONAL BUYING EFFECTIVENESS - Thongrawd, Chairit; Chomchom, Narumon; Phudetch, Pongtep; Somboon, Jureerut (International Journal of Supply Chain Management, 2019)
The study is intended to carry out to examine the mediating effect of the key supplier relationship management (KSRM) practices in the relationship between the supply chain orientation (SCO) and the organizational buying effectiveness (OBE). The study has used the SEM-PLS as a statistical tool to analyses the data. The findings of the study indicate that the value creation for customers is influenced through these dimensions of OBE in the following aspects: Value-oriented Purchasing: there is need for the purchasing managers to focus on the downstream supply chain side (customer) other than the upstream side during the procurement activities. Lateral involvement: specific knowledge is possessed by the employees of different departments related to the nature of products, which are purchased. Therefore, a deep insight is offered by them in the process of purchasing reflecting the qualities of products to be valuable for the customers. Information Sharing in Purchasing: distinct information is possessed by different employees on customer value. Purchasing effectiveness can be improved through sharing of information. The study which is among the pioneering studies in the issue will be helpful for the policy makers and researchers in understanding the issues related to key supplier relationship management (KSRM), supply chain orientation (SCO) and the organizational buying effectiveness.